Socioeconomic impact of the benefits and tax exemptions for the companies registered in the industrial park of the municipality of Level Cundinamarca. (2014)
The industrial park located in the town Cota – Cundinamarca, is a Project which has been developed since the late 90s and where it has been locating a number of companies and large multinational companies, this industrial park generates not only the benefit of being located in an excellent sector but also the town may generate Jobs, Social Inversion, Infrastructure, Economic Reactivation and else; these are goals that may be gotten through originated resources by taxes of the new companies which arrive to the town, it creates Agreements and Exemption Orders on the Industry and Commerce taxes, besides of benefits such as: maintenance of the road network, high quality utilities to be able exercising its economic activity, and if they provide employment to Cota habitants through employment office of the Secretariat of Agriculture, Environment and Economic Development, they may access to the incentive of the employability. To establish if those benefits and tax exemptions are really benefiting the town of Cota in its socioeconomic aspects, is realized an analysis about the statistics of the companies which are registered at the “Registro de Industria y Comercio” at the Secretariat of Finance of the town and where the agreements of tax incentives were emanated by the council of the town in Cota. With recorded values in database of Industry and Commerce at the Secretariat of Finance of the town from value of mentioned tax collection and of the exempt value starting with the Agreement #8 in June – 2004; it’s evaluated if politics, benefits and tax exemption assume the improvement of the conditions exposed before to the town of Cota or if the elimination of them, lead to a tax system more neutral.